1989
DOI: 10.1002/ana.410250204
|View full text |Cite
|
Sign up to set email alerts
|

Central effects of drugs used in migraine prophylaxis evaluated by visual evoked potentials

Abstract: The present study used recordings of visual potentials evoked by pattern reversal (VEPs) to investigate the central effects of three drugs used in migraine prophylaxis: the calcium channel blocker nifedipine, the beta-1-selective blocker metoprolol, and the nonselective beta adrenoreceptor blocker propranolol. The study involved 58 patients with common or classical migraine who were treated in a double-blind randomized study over a period of 7 months, while the effectiveness of prophylactic treatment was recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
85
3
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(98 citation statements)
references
References 16 publications
9
85
3
1
Order By: Relevance
“…Accordingly, the faster and smaller checksize stimulation by TVEP may play a crucial role in habituation behavior [14]. The present SSVEP study is in accordance with previous studies [30,35] that demonstrated greater migraine amplitude between attacks. Furthermore, the amplitude tended to increase depending on spatial frequency.…”
Section: Discussionsupporting
confidence: 93%
“…Accordingly, the faster and smaller checksize stimulation by TVEP may play a crucial role in habituation behavior [14]. The present SSVEP study is in accordance with previous studies [30,35] that demonstrated greater migraine amplitude between attacks. Furthermore, the amplitude tended to increase depending on spatial frequency.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, the prolonged CSP in our CM patients may point to an increased excitability of intracortical inhibitory neurons or axons. This finding, however, contradicts biochemical [7,9,22] and most of the neurophysiological studies [2,3,6,8,12,17,21,23, 35] on migraine suggesting increased cortical neuronal excitability. It has been shown that excitability increases with attack frequency in migraine [3,34,35].…”
Section: Discussioncontrasting
confidence: 73%
“…Several studies reported increased VEP amplitude in migraineurs (Diener et al, 1989;Khalil et al, 2000;Oelkers et al, 1999;Sand et al, 2008;Shibata et al, 1997Shibata et al, , 1998, while other studies could not confirm this (Coppola et al, 2007b;Kennard et al, 1978;Mariani et al, 1988;Oelkers-Ax et al, 2005;Polich et al, 1986;Sand and Vingen, 2000;Sener et al, 1997). In other words, the results of VEP measurements in migraine are contradictory in general, and not just regarding habituation.…”
Section: Visual Evoked Potential Amplitude In Migrainementioning
confidence: 96%